Application of thiabendazole/bentonites hybrids as efficient antibacterial agent against Escherichia coli and Staphylococcus aureus. (22nd December 2021) - Lin, Tao; Wang, Jun; Yin, Xuefeng; Wei, Xiaoyao
Abstract: Clay minerals are commonly used in agriculture, light industry, cosmetics, pharmaceuticals and other fields because it has adsorption and cation exchange properties. In this work, cetyltrimethylammonium bromide (CTAB) as a modifier and thiabendazole (TBZ) as intercalation agent to prepare composite, and their potential use as antibacterial agent was evaluated. Thiabendazole is a kind of antiparasitic drug which began to be used abroad in the early 60's. But soon after, it was discovered that it had a strong anti-fungal effect on many molds that affect vegetables, fruits, nuts and other crops. At present, it has been widely used in prevention and control abroad. Unmodified bentonite, modified bentonite and intercalated bentonite were characterized by x ray diffraction (XRD), Fourier transform infrared (FTIR), Energy dispersive x-ray spectroscopy (EDS) and Scanning electronic microscopy (SEM), and the antimicrobial properties of the compounds was investigated by Minimum inhibitory concentrations (MIC), Minimum bactericidal concentration (MBC) and Kirby-Bauer disc agar diffusion method. Among the three compounds, the ratio of modified bentonite to thiabenazole was 5:1 showed the highest antibacterial activity against Escherichia coli and Staphylococcus aureus . In the final, there are some figures about the SEM of E. coli and S. aureus that can indicate antibacterial of the antibacterial agent.